2018
DOI: 10.3390/molecules23071737
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Physicochemical Properties of Benzocaine Polymorphs

Abstract: The study was a pioneering attempt to assess the influence of the structural polymorphism (forms I, II, III) of benzocaine on its solubility, apparent solubility, and chemical stability, which are vital parameters for preformulation and formulation work. The impact of differences in the solubility of selected polymorphs of benzocaine on their permeability through artificial biological membranes (PAMPA system) was evaluated. The polymorphs of benzocaine were obtained by means of techniques commonly used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The current state of knowledge on the relationship between four BZC polymorphs was mapped in Scheme 1. Methods for ambient-pressure crystallization of polymorphs (I)-(III) are cited after previous reports (Sinha & Pattabhi, 1987;Lynch & McClenaghan, 2002;Chan et al, 2009;Paczkowska et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current state of knowledge on the relationship between four BZC polymorphs was mapped in Scheme 1. Methods for ambient-pressure crystallization of polymorphs (I)-(III) are cited after previous reports (Sinha & Pattabhi, 1987;Lynch & McClenaghan, 2002;Chan et al, 2009;Paczkowska et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Even slight changes in the hydrogenbonding pattern supporting the crystal structure, as observed between polymorphs, can result in varied properties of different solid forms of the same compound (Braga et al, 2009). In fact, it was recently reported that polymorphs (I)-(III) of BZC differ in solubility and permeability (Paczkowska et al, 2018). Until now three polymorphs of BZC were known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic bands in the range of ~450–1750 cm –1 and ~2770–3080 cm –1 were primarily considered. At ~850 cm –1 , the wagging vibrations of C–H bonds present in the benzene ring were identified [ 42 ]. Contrastingly, at 1102 cm –1 , the stretching vibrations of C–C bonds of the ring itself are noticed, which correspond to the breathing mode.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the bands centered at ~2895 and 2985 cm –1 assigned to the symmetric stretching vibrations of C–H from –CH 3 and the asymmetric stretching vibrations of C–H from –CH 2 are clearly visible. The pronounced three bands in the benzocaine FT-IR spectra at 3218, 3347, and 3427 cm –1 can be attributed to the symmetric and asymmetric stretching vibrations of N–H [ 42 ]. In the FT-IR spectra of all mesoporous carbon samples registered after the adsorption of benzocaine, some new bands derived from the active substance become visible, especially in the wavenumber range of ~450–1750 cm –1 .…”
Section: Resultsmentioning
confidence: 99%